ChemInform Abstract: Room‐Temperature ortho‐Alkoxylation and ‐Halogenation of N‐Tosylbenzamides by Using Palladium(II)‐Catalyzed C—H Activation. Issue 50 (16th December 2014) - Peron, Florent; Fossey, Christine; Sopkova‐de Oliveira Santos, Jana; Cailly, Thomas; Fabis, Frederic
Abstract The Pd‐catalyzed oxidative ortho‐alkoxylation of N‐tosylbenzamides is developed to give good yields and selectivity.